Pressure-induced amorphous-amorphous transition in pre-densified silica glass: an experimental exploration of the potential energy landscape - M. Courtois; A. Berthelot; A. Cornet; S. Le Floch; C. Martinet; T. Deschamps (Scientific Reports)
Abstract Despite the difficulty of experimentally studying polyamorphic transitions in high-Tg glasses, it is well known that silica glass has two high-density phases: the cold-compressed and hot-compressed high-density amorphous phases (c-HDA and h-HDA). By means of vibrational spectroscopy techniques under pressure, we first evidence that the yield strength under hydrostatic pressure is identical for glasses of similar density, whatever the thermo-mechanical history, showing that the elastic limit of a silica glass depends solely of its density. Our results also reveal the changes in the energy landscape of amorphous silica under high pressure. Above a certain threshold pressure, the energy barriers between the different amorphous phases vanish and the glass is automatically driven toward the c-HDA phase, whatever the initial structure and the temperature of compression. Very high pressures can therefore erase all traces of a glass’s thermodynamic history.